In vitro evaluation of three-dimensional printed thermoplastic polyurethane and polylactic acid scaffold for tracheal tissue engineering - Abdul Samat, Asmak; Yahaya, Badrul Hisham; Abdul Hamid, Zuratul Ain; Jaafar, Mariatti (2022)
Introduction: Three dimensional (3D) printed scaffold using polymer composite is a potential technique for the replacement and regeneration of damaged tissue. The scaffolds must meet several requirements to be physiologically functional to provide an ideal environment for cells and act as a vital physical substrate for cell attachment, proliferation, differentiation, and integration into the host tissue. These include degradable, nontoxicity, and a favourable surface for cell-matrix adhesion and proliferation. The purpose of this study was to evaluate the cell proliferation and attachment of the 3D-printed TPU/PLA scaffolds in a cell culture experiment. Methods: 3D printing was performed through the fused deposition modelling (FDM) technique using our custom-made thermoplastic polyurethane (TPU) and polylactic acid (PLA) filaments. The degradation rate was determined, and the pH of the extracts was evaluated towards the proliferation of human normal bronchial epithelial cells (BEAS2B). Direct cell attachment of the cells on the scaffolds was also assessed. Results: The viability of cell culture is shown by the proportion of viable cells in a population. BEAS-2B was cultured for three days on sterilised TPU, PLA, and TPU/PLA scaffolds to test their biocompatibility and toxicity of the material. Both pure TPU and PLA indicated biocompatibility towards BEAS-2B cells. The result showed that the viability of BEAS-2B was greater than 80% in all compositions up until day 3, indicating that none of the compositions was toxic to the cells. The study was demonstrated that the degradation and pH of the TPU/PLA did not affect cell proliferation and attachment. Conclusion: This study concluded that 3D printed TPU and PLA composite had a promising property and were suitable for future applications in tracheal tissue engineering.